CERVICAL ECTOPIC PREGNANCY: http://doi.org/10.46536/jpumhs/2024/14.02.525 - Raana Bibi Niazi (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
Less than 0.1% of pregnancies result in ectopic cervical pregnancy (CP), a rare disease. It is linked to possibly elevated rates of morbidity and mortality. The difficulties in diagnosis and treatment are addressed in this case report on cervical pregnancy, along with the course of follow-up and ultimate result. After presenting with vaginal bleeding, a 30-year- old lady was diagnosed with an impending miscarriage and treated conservatively rather than surgically. Cervical ectopic pregnancy was diagnosed during the clinical examination, confirmed by ultrasound on the second day of hospitalization, and successfully treated surgically.The follow up went smoothly and had good outcomes.